Designing Learning Materials of Indonesian Language Course based on Augmented Reality and Interactive Website for Blind Students - Hasanudin, Cahyo; Fitrianingsih, Ayu; Sholehhudin, Muhamad; Ulfaida, Nabila (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Indonesian language is a compulsory subject in university level. This subject has been taken by all Indonesian university students with or without disabilities. This study aimed to design Indonesian Language course based on Augmented Reality (AR) and interactive website that were adapted for blind students. This study was developmental research using ADDIE model. The subjects of this study were students with disabilities in private universities at East Java, Indonesia. Result of study showed that in analysis stage there were five things needed by disability students. In the design stage, flowchart and storyboard were made. In the developmental stage, website structures were built using WordPress; while Augmented Reality was designed using Unity platform. In the implementation stage, limited and extensive trial tests were conducted. In the evaluation stage, there were two main activities. First, students were given tests. Second, product was revised. Conclusion of this study was learning materials of Indonesian language course could be developed by implementing ADDIE model, so it could be used by blind students.